Regional Tax and Economic Growth in Indonesia - Samudro, Herry (JURNAL PAJAK INDONESIA, 2024)
Indonesia targets economic growth to increase continuously every year, but on the other hand, state revenues depend on taxes. Almost 80% of state revenue comes from taxes and this will certainly have an impact on economic growth in Indonesia. The amount of tax applied to society can have a positive or negative effect on economic growth, depending on how the country uses the tax revenue. In theory, a country's economic growth can be seen from the amount of regional tax revenue in that country, the regional work participation rate, the human development index in the region, the poverty level in the region, and the regional Gini ratio. So, in this research, the author wants to test the influence of the factors above on economic growth in Indonesia. The author uses secondary data from 34 provinces in Indonesia from 2018 to 2022 which comes from the Directorate General of Fiscal Balance (Ministry of Finance) and Statistics Indonesia. The results of this research show that regional tax revenues have a negative effect on economic growth in Indonesia. The same thing is also shown by the factors of work participation rate, human development index in the region, poverty level in the region, and regional Gini ratio which have a negative influence on economic growth.